Ancient Khmer elephant-jar reflects potters' brilliance - Rooney, Dawn.
Dawn Rooney reports on the background of the discovery of a unique Khmer elephant-jar, its technical characteristics, iconography, and possible meaning and function in Khmer society.
Keywords: Khmers; Pottery, Khmer; Pottery; Potters; Ceramics